2020
DOI: 10.1155/2020/3286139
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Immunohistochemistry Comparability and Their Correlation with Clinical Characteristics in NSCLC

Abstract: Background. PD-L1 expression is an important predictive factor of response to therapy with immune checkpoint inhibitors (ICIs). This study was designed to retrospectively analyze the concordance of PD-L1 measurements using three different assays (Dako22C3, Dako28-8, and SP142) in NSCLC patients and to find possible predictors of high PD-L1 expression. Materials and Methods. Data of 144 patients with histologically confirmed NSCLC and available PD-L1 measurements treated at the Taoyuan General Hospital from 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…In the pan-cancer analysis of ICOS expression in this study, we also found that ICOS was expressed at lower levels in lung tissues. In addition, low ICOS expression indicated high-grade NSCLC progression in the T stage, while high PD-L1 expression indicated high-grade in the N stage, which is consistent with one report of 144 patients with lung cancer, which showed that PD-L1 expression in NSCLC was associated with a higher N stage, but not the T and M stages [30].…”
Section: Discussionsupporting
confidence: 90%
“…In the pan-cancer analysis of ICOS expression in this study, we also found that ICOS was expressed at lower levels in lung tissues. In addition, low ICOS expression indicated high-grade NSCLC progression in the T stage, while high PD-L1 expression indicated high-grade in the N stage, which is consistent with one report of 144 patients with lung cancer, which showed that PD-L1 expression in NSCLC was associated with a higher N stage, but not the T and M stages [30].…”
Section: Discussionsupporting
confidence: 90%
“… 14 In non-small cell lung cancer (NSCLC), PD-L1 levels were correlated with N, but not T or M stage. 15 These data suggest that, in certain types of tumor, PD-L1 level may be related to tumor stage, and could be more significant only in certain stages. Whether PD-L1 expression in different tumor stages can be applied to the evaluation of immunotherapy warrants further study.…”
Section: Pd-l1 Expression In Different Tumor Stagesmentioning
confidence: 80%
“…Third, pathology‐based immune cell PD‐L1 scoring has repeatedly shown poor reproducibility in SCLC, thus restricting PD‐L1’s utility as a biomarker in SCLC [ 28 , 29 ]. Fourthly, PD‐L1 detection reagents and platforms are also diverse to date, with pembrolizumab and nivolumab using Dako22C3 and Dako28‐2 PD‐L1 detection reagents respectively, and atezolizumab and durvalumab using SP263 detection antibodies, and consistency studies of detection antibodies and platforms urgently need to be conducted [ 30 ]. Therefore, the use of PD‐L1 as a biomarker still faces many challenges, and there are no criteria for determining a positive cut‐off value for PD‐L1 expression.…”
Section: Discussionmentioning
confidence: 99%